2013
DOI: 10.1371/journal.pone.0082773
|View full text |Cite
|
Sign up to set email alerts
|

TP53 and MDM2 Gene Polymorphisms, Gene-Gene Interaction, and Hepatocellular Carcinoma Risk: Evidence from an Updated Meta-Analysis

Abstract: BackgroundThe association between TP53 R72P and/or MDM2 SNP309 polymorphisms and hepatocellular carcinoma (HCC) risk has been widely reported, but results were inconsistent. To clarify the effects of these polymorphisms on HCC risk, an updated meta-analysis of all available studies was conducted.MethodsEligible articles were identified by search of databases including PubMed, Cochrane Library, EMBASE and Chinese Biomedical Literature database (CBM) for the period up to July 2013. Data were extracted by two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…According to the publicly available databases (e.g., Sanger), mutations or deletions of the human MTBP genes are rare events. However, the prior study has demonstrated that MDM2 SNP309 polymorphism may play an important role in the carcinogenesis of HCC [25].…”
Section: Discussionmentioning
confidence: 93%
“…According to the publicly available databases (e.g., Sanger), mutations or deletions of the human MTBP genes are rare events. However, the prior study has demonstrated that MDM2 SNP309 polymorphism may play an important role in the carcinogenesis of HCC [25].…”
Section: Discussionmentioning
confidence: 93%
“…Many studies including meta-analyses have shown relationships between SNPs and human cancer susceptibility [21][22][23][24][25]. For these SNPs to be useful biomarkers, they should be validated in several populations because of racial differences [26].…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 prevents the activity of the tumor suppressor p53; therefore, amplification of MDM2 may be oncogenic 22 and may predict sensitivity to MDM2 inhibitors. However, currently available evidence is inconclusive 23.…”
Section: Discussionmentioning
confidence: 99%